2007
DOI: 10.1007/s11906-007-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of salt-sensitive hypertension

Abstract: Excess dietary salt intake represents a predominant cause of hypertension. However, individual blood pressure response to salt is heterogeneous, possibly due to different inherited susceptibility. The early identification of rare monogenic forms of hypertension associated with abnormalities of renal tubular sodium handling and response to diuretics highlighted the important role of renal alterations in salt-sensitive hypertension. Thereafter, interest has concentrated on the identification of more common allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 67 publications
2
28
0
1
Order By: Relevance
“…[24,25] This further strengthens the concept that Na + intake in hypertensives can never be a fixed quantity for all humans as it is genetically (mono as well as polygenetically) determined also. Besides evidence also indicates that complex interactions among multiple genes might also affect the salt sensitivity of an individual.…”
Section: Rare Cause Of Extreme Dietary Sodium Restriction (Anorexia Nsupporting
confidence: 72%
See 1 more Smart Citation
“…[24,25] This further strengthens the concept that Na + intake in hypertensives can never be a fixed quantity for all humans as it is genetically (mono as well as polygenetically) determined also. Besides evidence also indicates that complex interactions among multiple genes might also affect the salt sensitivity of an individual.…”
Section: Rare Cause Of Extreme Dietary Sodium Restriction (Anorexia Nsupporting
confidence: 72%
“…Besides evidence also indicates that complex interactions among multiple genes might also affect the salt sensitivity of an individual. [24,25] There is no unanimity and consensus in the definition of salt sensitivity from the available literature so far. [26][27][28] However, Weinberger [28] classified salt sensitive individuals as those in whom there is 10% increase in mean arterial pressure when the low (9 mmol/day) and high salt (249 mmol/day) pressures were compared.…”
Section: Rare Cause Of Extreme Dietary Sodium Restriction (Anorexia Nmentioning
confidence: 99%
“…In the absence of any other manipulation, it has been shown that high sodium intake alone can promote hypertension in rats, chimpanzees, pigs, and African Green Monkeys [36,[50][51][52][53][54]. Both human and animal studies have provided evidence that there may be a strong genetic component underlying the susceptibility to salt-sensitive hypertension [52,[55][56][57].…”
Section: Pathophysiology Of Excess Sodium Intakementioning
confidence: 99%
“…Several studies have been performed to identify genetic factors that may contribute to salt sensitivity, but the results have not been consistent (Strazzullo and Galletti 2007), possibly due to the difficulty in defining the phenotype. To overcome this problem, a homogeneous population of SS and SR hypertensive patients and normotensive controls was recruited that did not differ for ethnicity, age, sex, or body mass index.…”
Section: Discussionmentioning
confidence: 99%